Kliničko posmatranje laparoskopskih gastrectomija rukava i metforminov tretman kod gojaznih PCOS pacijenata: Laparoscopic Sleeve Gastrectomy and Metformin in PCOS Obese - Ma, Qingya; He, Xiaojing; Fu, Zijie; Ren, Xiaodong; Sun, Ranran; Zhu, Siqi; Li, Xiaodong; Bian, Yahui (Journal of Medical Biochemistry, 2023)
Background: to observe the basic metabolic characteristics of obese patients with PCOS, and observe and compare the effect of laparoscopic sleeve gastrectomy and metformin treatment after 3 months.Methods: In January to December 2018, the Second Hospital of Hebei Medical University selected 104 women who were classified as obese with a BMI of 28kg/cm2 or higher and had PCOS. They were divided into obese PCOS group (53 cases) and obese non-pcos group (51 cases).Results: 1. There was no significant difference in waist circumference and WHR between patients who are obese with PCOS and patients who are obese without PCOS (P > 0.05).Obese PCOS patients were significantly higher in AMH, LH/FSH, T, FAI, homa-ir, TG, LDL, apo-b and uric acid than the group of non-PCOS patients who were obese. (P